A Scientometric Review of Digital Currency and Electronic Payment Research: A Network Perspective. (9th November 2020) - Shi, Qing; Sun, Xiaoqi
Abstract : The potential implications of digital currencies and electronic payment (DC/EP) have become a hot global research area. To present the knowledge bases and research fronts of this field, we apply a scientometric approach to analyze 454 publications obtained from the Web of Science core collection. Results show that, first, the knowledge bases can be classified into three main topics: (1) the usage and diversification effect of private digital currencies from the point of investment and asset allocation; (2) the price dynamics and market efficiency of private digital currencies; and (3) other economic roles of digital currencies and corresponding change brought into the monetary system. Second, several research trends can be inferred using sliding window analysis and burst detection, namely, how the introduction of digital currencies changes consumers' choice in payment instrument and their money demand; how social media and investor sentiment affect the market of digital currencies; and the impact of digital currencies on the central bank, monetary policy, and central bank digital currency. Third, core scholars and countries involved in the research of DC/EP are identified, and it is found that collaboration has been rising especially among European scholars and countries. With these systematic analyses, we offer recommendations for scholars and practitioners in future research of DC/EP.